An analysis of decision – making structure for self-organizing system based on software engineering. (January 2017) - Babu, S.; Lakshmi, N.V.S. Sree Rathna; Sivakumar, B.
Abstract: One of the most important parts in developing any kind of software is to check the sustainability of the software which is done by the software testing by the software engineers. A varied number of test cases have been taken into account and the test is done by using the Unified Modelling language (UML). By using the combination of the hybrid revised genetic algorithm along with the Bee Colony Optimization, the test has come out to be in the favour of finding the maximum and the minimum coverage. This novel approach has been tested over the application of a Smart Card users/Security Token user. In order to increase the security of the Smart Card/Security Token (SC/ST), a novel approach for Smart Card/Security Token (SC/ST) has been proposed, is a decision making structure for self- organising systems based on Software Engineering. By this secured details can be obtained from the total number of smart card users. By this approach, the total flaws present in the system can be easily detected along with the maximum possible paths. The novel technique for software testing guarantees that minimum time has been considered for maximum coverage.